Prevalence and risk factors of retinopathy of prematurity - Cut Badriah; Idham Amir; Elvioza Elvioza; Evita Ifran (Indonesian Pediatric Society, 2012)
Background Retinopathy of prematurity (ROP) is the main causeof visual impairment in premature infants. Due to advances inneonatal care, the increased survival of extremely low birth weight(ELBW) infants in recent years has produced a population ofinfants at very high risk of ROP.Objective The aims of this study were to determine theprevalence and potential risk factors for ROP.Methods This retrospective study was conducted at theNeonatalogy Ward, Cipto Mangunkusumo Hospital, fromJanuary 2005 to August 2010. We included all prematureinfants of gestational age (GA) < 37 weeks, body weight(BW) not exceeding 2000 grams, as well as those who hadeye examinations and complete medical records. Risk factorssuch as GA, BW, duration of oxygen (Oz) therapy, sepsis, andred blood cell (RBC) transfusion were analyzed using the Chiô€€»square and logistic regression tests. Pediatric ophthalmologistshad performed eye examinations on all infants. ROP was gradedaccording to the International Classification of ROP.Results The prevalence of ROP and of stage 3 or greaterROP was 11.9% and 4.8% of all subjects, respectively. Bodyweight, GA, duration of Oz therapy, and sepsis were found tobe associated with the development ofROP. However, stepwiselogistic regression analysis revealed that only BW of:s 1000g [odds ratio (OR) 10.88; 95% CI 3.09 to 38.31; P < 0.000],02 therapy 2: 7 days (OR 5.56; 95% CI 1.86 to 16.58; P <0.0001), and GA of oS 28 weeks (OR 4.26; 95% CI 1.15 to15.81; P = 0.030) were statistically significant risk factors forROP. The equation obtained was y ô€€ƒ -4.092 + 2.388 (BW)+ 1.451 (GA) + 1.716 (duration of 02 therapy). The modelshowed good calibration (a nonô€€»significant Hosmerô€€»Lemeshowtest; P = 0.816) and discriminative ability. The area underthe curve (AUC) value was 92.2% (95% CI 0.867 to 0.976;P < 0.0001).Conclusion Prevalence ofROP in this study (11.9%) was lowerthan that of previous studies. By regression logistic analysis, themain risk factors for development ofROP were BW of:s 1000g, Oz therapy 2: 7 days, and GA :s 28 weeks. The probability ofROP occurrence increased v.ith greater number of risk factors.[Paediatr rndones. 2012;52:138-44].